The Effect of Human Capital Management on Employee Performance with Job Satisfaction as an Intervening Variable (Case Study at the head office of PT. Perkebunan Nusantara IX Semarang) - Yuri Rizki Pratama; Berry Lesmana (Journal of Applied Digital Business Management, 2024)
The plantation industry plays an essential role in national development, especially in the regional sector, absorbing labor and increasing income. Therefore it is essential to improve the existing human resources in the company. This study aims to determine the effect of Human Capital Management, Job Satisfaction, and Employee Performance. This research is descriptive verification research by distributing questionnaires to 122 employees at PTPN IX Semarang. This test is carried out using path analysis. The results of the analysis of the research show that Human Capital Management influences job satisfaction with a path coefficient value of 0.745. Then the job satisfaction variable influences employee performance with a path coefficient value of 0.721. Based on the calculated Z value of 7.256, it explains that Human Capital Management influences employee performance at PTPN IX Semarang through job satisfaction.